PENGARUH BEBAN KERJA DAN KECERDASAN EMOSIONAL TERHADAP WORK LIFE BALANCE PADA PELAUT DI KAPAL KARGO - Alvin Aditya Reynaldi; Rini Nurahaju; Dessy Nur Utami (Fakultas Psikologi Universitas Hang Tuah, 2022)
This study aims to determine whether workload and emotional intelligence are factors that can affect the work life balance of seafarers on cargo ships. The hypothesis proposed in this study is that there is an effect of workload and emotional intelligence together on the work life balance of seafarers on cargo ships. This research uses a quantitative approach with a survey method. This study uses multiple linear regression analysis. The number of subjects in this study were 73 respondents who were sailors on a sea toll ship (cargo) owned by PT PELNI (Persero) Surabaya Branch. The sampling technique used is saturated sampling technique and data collection technique with 3 (three) scales, namely workload, emotional intelligence, and work life balance. The results of hypothesis testing on workload and emotional intelligence together are predictors of work life balance on seafarers on cargo ships.